PENINGKATAN PEMBELAJARAN AGAMA ISLAM MELALUI METODE PEMBERIAN TUGAS BELAJAR DAN RESITASI - Kursiti Kursiti (Asaatidzah, 2023)
This study aims to describe methods of giving learning assignments and recitations as well as to find out learning enhancement activities for class VII students of SMPN Panguragan, Cirebon Regency, in the 2019/2020 academic year. This research is an action research class subject to PAI (Islamic Religious Education), which starts from the stages of planning, implementing action, observing and reflecting. The research subjects in class A were 30 students of class VII SMPN Panguragan, Cirebon Regency. Methods of data collection using observation, tests, interviews, and documents. The data analysis used was descriptive with a qualitative approach. The results of the research show that the recitation method can increase student learning activities and outcomes. In the first cycle of student learning activities in the medium category, namely 2.1 and the second cycle increased by 3.1 in the high category. Student learning outcomes in cycle I showed an average score of 76.4 students with classical learning mastery of 77.5% and cycle II increased by 81.8 with classical learning mastery of 82.8%.